2018
DOI: 10.1128/aem.00235-18
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of Oxo-Bile Acids and Characterization of Recombinant 12α-Hydroxysteroid Dehydrogenases from Bile Acid 7α-Dehydroxylating Human Gut Bacteria

Abstract: Bile acids are important cholesterol-derived nutrient signaling hormones, synthesized in the liver, that act as detergents to solubilize dietary lipids. Bile acid 7α-dehydroxylating gut bacteria generate the toxic bile acids deoxycholic acid and lithocholic acid from host bile acids. The ability of these bacteria to remove the 7-hydroxyl group is partially dependent on 7α-hydroxysteroid dehydrogenase (HSDH) activity, which reduces 7-oxo-bile acids generated by other gut bacteria. 3α-HSDH has an important enzym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
81
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 80 publications
(96 citation statements)
references
References 57 publications
5
81
1
2
Order By: Relevance
“…Doubling times for cells grown in BHI, UM, DM, and PO 4 -buffered DM approximated 2.0, 2.3, 3.3, and 7.0 h, respectively. While previous work has shown that CA is 7␣-dehydroxylated to DCA by cells grown in BHI medium (15), we report here CA conversion to DCA by C. scindens ATCC 35704 grown in a defined or minimal medium ( Fig. 1B).…”
Section: Resultscontrasting
confidence: 51%
See 3 more Smart Citations
“…Doubling times for cells grown in BHI, UM, DM, and PO 4 -buffered DM approximated 2.0, 2.3, 3.3, and 7.0 h, respectively. While previous work has shown that CA is 7␣-dehydroxylated to DCA by cells grown in BHI medium (15), we report here CA conversion to DCA by C. scindens ATCC 35704 grown in a defined or minimal medium ( Fig. 1B).…”
Section: Resultscontrasting
confidence: 51%
“…1C). The bile acid concentration chosen reflects both in vivo physiologically relevant concentrations of bile acids in fecal water (18,19) and concentrations used previously in numerous in vitro studies of C. scindens strains (6,10,15). Separate additions of CA in early and mid-log phase have been previously shown to result in robust induction of the bai regulon (7).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To determine how widely genes encoding for bile acid pathways are spread in human gut microbes, we performed a systematic comparative genomic analysis of the bile acid deconjugation and transformation pathway ( Fig. 2), starting with previously characterized enzymes for primary bile acid deconjugation [21] and transformation into secondary bile acids [22][23][24][25]. Of the currently 818 microbial AGORA reconstructions, which include 46 newly reconstructed gut microbes (see the "Materials and methods" for details), only 670 genomes were available at the PubSEED database [26,27].…”
Section: Distribution Of Microbial Bile Acid Deconjugation and Biotramentioning
confidence: 99%